An optical adhesive film suitable for full lamination process

By adopting a three-layer structure optical adhesive film, using the adhesive film raw materials and light-induced polymerization process of specific formulas, the poor bonding and bubble generation problems of the existing optical adhesive film in the full bonding process are solved, and good display effect and decomposition are achieved.

CN119752331APending Publication Date: 2025-04-04SUZHOU FINESET MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411969424.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing optical adhesive films have problems such as poor bonding and bubble generation in the full bonding process, resulting in defective products or scrapping, and the existing disassembly methods consume high energy or affect the performance of the module.

Method used

The optical adhesive film with a three-layer structure is adopted, and the adhesive film raw material formula of the intermediate layer and the outer layer on both sides includes C4-C18 acrylate monomer, hydrophilic monomer, acidic/alkaline monomer, crosslinking agent and photoinitiator, respectively, which are prepared by photoinitiation polymerization and defoaming processes to improve the adhesion and decomposition of the adhesive film.

Benefits of technology

The optical adhesive film has achieved good display effect, excellent reliability and good rework effect in the full bonding process, reducing energy consumption during bubble generation and disassembly, and improving the protection of module performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219168480000081
    Figure BDA0005219168480000081
Patent Text Reader

Abstract

The present invention discloses an optical adhesive film suitable for a full lamination process, wherein the adhesive film has a three-layer structure, wherein the raw materials of the adhesive film of the middle layer include the following components by weight: 80%-90% C4-C18 acrylate monomer I; 5%-15% hydrophilic monomer I; 1%-10% acidic monomer; 0.05-0.5% crosslinking agent I; 0.05-0.5% photoinitiator I; the raw materials of the adhesive films of the outer layers on both sides include the following components by weight: 80%-90% C4-C18 acrylate monomer II; 5%-15% hydrophilic monomer II; 1%-5% basic monomer; 0.05-0.5% crosslinking agent II; 0.05-0.5% photoinitiator II. The adhesive film obtained by the present invention has the advantages of good display effect, excellent reliability and good rework effect when matched with a display device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical adhesives, and in particular to an optical adhesive film suitable for a full-bonding process. Background Art

[0002] In the field of optical adhesive technology, optical adhesive is a material commonly used to fix and connect optical components. In display screens and other devices, optical adhesive is widely used in the assembly process of LCD screens and touch screens. OCA optical adhesive has the advantages of colorless transparency, high transmittance, low haze, and good yellowing resistance.

[0003] During the full bonding process, there are usually poor bonding or bubbles or other defects after bonding, resulting in defective or scrapped products. Since the display module is of high value, the defective or scrapped products must be disassembled and re-bonded, so the disassembly of OCA is required. In the disassembly process, there are currently two types of cold disassembly and hot disassembly. The former is to place the defective product in an ultra-low temperature environment (usually below -100°C) to make the OCA lose its viscosity, so as to separate the module and OCA first, and then heat up to separate the OCA from the glass cover. However, this method has the defect of high energy consumption, and the ultra-low temperature environment also has a certain impact on the performance of the module. The latter is to place the defective product on a 70-90°C disassembly platform, cut the OCA in the middle with a metal wire, and then clean up the remaining OCA on the film group or cover. This method is simple and convenient and is the mainstream method of disassembly at present.

[0004] At present, as reported in CN 117820971 A, different OCA adhesive layers are prepared on both sides of a PET substrate. The two OCA adhesive layers are designed with different raw materials and proportions. The side bonded to the ultra-thin glass cover plate uses the chemical bond formed between polar groups (such as hydroxyl groups) and inorganic substances for attachment; the other side is bonded to an organic film material (CPI), which uses molecular similarity for attachment. In addition, the present invention takes into account the Tg point, creep and recovery properties of OCA, and uses light initiation to control Tg when synthesizing prepolymers, so as to achieve rapid creep and recovery and avoid material residue. However, the bonding force between the two side layers and the middle layer is weak, and bubbles are easily generated during the RA process.

[0005] CN 118685121 A reports a double-layer OCA optical adhesive and a preparation method, which comprises an optical light release film, a filling layer acrylate polymer layer, a stretching layer acrylate polymer layer, and an optical heavy release film. It solves the problem of improving the filling performance and tensile strength of the adhesive by improving the formula and production process of the adhesive in the prior art. It solves the problem that the single-layer structure requires a high cost and has limited effect, and solves the problem that due to the nature of the adhesive, once the adhesive is bonded, it is difficult to disassemble again, which brings great inconvenience to the maintenance and replacement of the product. However, during the hot disassembly process, after the metal wire is divided, the interlayer structure is destroyed, the stretching layer is mainly concentrated on the surface of the polarizer, and the high filling layer remains on the cover surface, making it more difficult to disassemble.

[0006] CN 118685119 A reports a method of providing a removable three-layer adhesive film, which is obtained by laminating OCA film 1, OCA film 2, and OCA film 3 in sequence. The adhesive layers in OCA film 1, OCA film 2, and OCA film 3 are all obtained by solvent-based polymerization, which has a strong odor and poor environmental testing effect. In addition, the three-layer adhesive film needs to be superimposed and compounded, and the entire preparation process is cumbersome and the cost is extremely high.

[0007] How to solve the above technical problems is the research direction that technicians in this field are committed to. Summary of the invention

[0008] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an optical adhesive film suitable for a full-lamination process, which has the advantages of good display effect, excellent reliability and good rework effect when matched with a display device.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is: an optical adhesive film suitable for full bonding process, the adhesive film has a three-layer structure, wherein:

[0010] The raw materials of the adhesive film of the middle layer include the following components in parts by weight:

[0011] 80%-90% C4-C18 acrylate monomer I; 5%-15% hydrophilic monomer I; 1%-10% acidic monomer; 0.05-0.5% crosslinker I; 0.05-0.5% photoinitiator I;

[0012] The raw materials of the adhesive films on both sides include the following components by weight:

[0013] 80%-90% C4-C18 acrylate monomer II; 5%-15% hydrophilic monomer II; 1%-5% basic monomer; 0.05-0.5% crosslinking agent II; 0.05-0.5% photoinitiator II.

[0014] As a specific implementation, both photoinitiator I and photoinitiator II use hydrogen abstraction type photoinitiators or cleavage type photoinitiators.

[0015] As a specific implementation method, the preparation process of the adhesive film of the middle layer is as follows:

[0016] In a reaction vessel equipped with a thermometer, a stirring device and a nitrogen injection tube, C4-C18 acrylate monomer I, hydrophilic monomer I, acidic monomer and part of photoinitiator I were added, and nitrogen was replaced at a wind volume of 100 mL / min while stirring and mixing evenly. Then, at 1.0 mW / cm 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 15%, and then the crosslinking agent I and the remaining photoinitiator I were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain the adhesive resin composition I required for the middle layer;

[0017] After that, the adhesive resin composition I obtained above was dripped onto the PET release film, and then another PET release film was covered on the other side of the adhesive resin composition I. The adhesive resin composition I was coated into a sheet with a thickness of 50 μm using a roller, and ultraviolet rays were irradiated using an ultraviolet irradiation device with an irradiation intensity of 5 W / cm 2 , energy is 300mJ / cm 2 , a transparent adhesive sheet is obtained;

[0018] The preparation process of the adhesive films on both sides is as follows:

[0019] In a reaction vessel equipped with a thermometer, a stirring device and a nitrogen injection tube, C4-C18 acrylate monomer II, hydrophilic monomer II, basic monomer and part of photoinitiator II were added, and nitrogen was replaced at a wind volume of 100 mL / min while stirring and mixing evenly. Then, at 1.0 mW / cm 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 18%, and then the crosslinking agent II and the remaining photoinitiator II were added. After stirring and dissolving evenly, the mixture was degassed under a vacuum of 0.95 MPa for 2 hours to obtain the adhesive resin composition II required for the outer layer.

[0020] After that, the adhesive resin composition II obtained above was dripped onto the PET release film, and then another PET release film was covered on the other side of the adhesive resin composition II. The adhesive resin composition for the adhesive sheet was coated into a sheet with a thickness of 50 μm using a roller, and ultraviolet rays were irradiated using an ultraviolet irradiation device with an irradiation intensity of 5 W / cm 2 , energy is 300mJ / cm 2 , a transparent adhesive sheet was obtained.

[0021] Due to the application of the above technical scheme, the present invention has the following advantages compared with the prior art: the optical adhesive film of the present invention adopts a three-layer structure of a middle layer and outer layers on both sides. The film has the advantages of good display effect, excellent reliability and good repair effect when matched with a display device. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0023] The following provides an optical adhesive film suitable for full lamination process, the adhesive film has a three-layer structure, wherein:

[0024] The raw materials of the adhesive film of the middle layer include the following components in parts by weight:

[0025] 80%-90% C4-C18 acrylate monomer I; 5%-15% hydrophilic monomer I; 1%-10% acidic monomer; 0.05-0.5% crosslinker I; 0.05-0.5% photoinitiator I;

[0026] The raw materials of the adhesive films on both sides include the following components by weight:

[0027] 80%-90% C4-C18 acrylate monomer II; 5%-15% hydrophilic monomer II; 1%-5% basic monomer; 0.05-0.5% crosslinking agent II; 0.05-0.5% photoinitiator II.

[0028] Example 1

[0029] This example provides a three-layer optical adhesive film, the preparation method of which includes the following steps:

[0030] 1) Preparation of intermediate layer OCA film I:

[0031] In a reaction vessel equipped with a thermometer, a stirrer, and a nitrogen injection tube, 80.0 g of isooctyl acrylate, 15 g of hydroxyethyl acrylate, 5.0 g of acrylic acid, and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 15%. Then, 0.2 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0032] Thereafter, the adhesive resin composition for an adhesive sheet obtained above was dripped onto a polyethylene terephthalate (PET) release film (the release surface was in contact with the adhesive resin composition), and then another PET release film was covered thereon (the release surface was in contact with the adhesive resin composition). The adhesive resin composition for an adhesive sheet was applied to a sheet with a thickness of 50 μm using a roller, and ultraviolet rays were irradiated using an ultraviolet irradiation device (intensity of 5 W / cm 2 , energy is 300mJ / cm 2 ) to obtain a transparent adhesive sheet.

[0033] 2) Preparation of outer layer OCA film II:

[0034] In a reaction vessel equipped with a thermometer, a stirrer and a nitrogen injection tube, 83.0 g of isooctyl acrylate, 15 g of hydroxyethyl acrylate, 2.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED lamp to increase the solid content to 18%. Then, 0.05 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0035] Then, the adhesive resin composition for adhesive sheet obtained above was dripped onto a polyethylene terephthalate (PET) release film (the release surface was in contact with the adhesive resin composition), and then another PET release film was covered thereon (the release surface was in contact with the adhesive resin composition). The adhesive resin composition for adhesive sheet was applied into a sheet with a thickness of 50 μm using a roller, and ultraviolet rays were irradiated using an ultraviolet irradiation device (intensity of 5 W / cm 2 , energy is 300mJ / cm 2 ) to obtain a transparent adhesive sheet.

[0036] The adhesive surfaces of OCA film 1 and OCA film 2 are laminated and stacked to obtain a semi-finished product; then another release film on OCA film 1 is peeled off from the semi-finished product, and the exposed adhesive surface is laminated to the adhesive surface of OCA film 2 to obtain a three-layer structure finished product.

[0037] Example 2

[0038] 1) Preparation of intermediate layer acrylic resin I:

[0039] In a reaction vessel equipped with a thermometer, a stirrer, and a nitrogen injection tube, 80.0 g of isooctyl acrylate, 15 g of hydroxyethyl acrylate, 5.0 g of acrylic acid, and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 15%. Then, 0.2 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0040] 2) Preparation of outer layer acrylic resin II:

[0041] In a reaction vessel equipped with a thermometer, a stirrer and a nitrogen injection tube, 83.0 g of isooctyl acrylate, 15 g of hydroxyethyl acrylate, 2.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED lamp to increase the solid content to 18%. Then, 0.05 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0042] The middle layer acrylic resin I and the outer layer acrylic resin II are pumped into the middle cavity and the upper and lower side cavity of the three-layer co-extrusion coating head respectively, and sprayed on the heavy release film through the lip of the coating head, and then covered with the light release film, and finally put into the UV light oven for curing and winding to obtain a three-layer optical adhesive film. The thickness between each layer can be adjusted by the pumping flow of each layer, and the thickness of each layer of the final three-layer optical adhesive film is set to 50μm / 50μm / 50μm.

[0043] Example 3

[0044] 1) Preparation of intermediate layer acrylic resin I:

[0045] In a reaction vessel equipped with a thermometer, a stirrer, and a nitrogen injection tube, 85.0 g of isooctyl acrylate, 10 g of hydroxyethyl acrylate, 6.0 g of acrylic acid, and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2The mixture was polymerized under a 365 nm LED light to increase the solid content to 15%. Then, 0.2 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0046] 2) Preparation of outer layer acrylic resin II:

[0047] In a reaction vessel equipped with a thermometer, a stirrer, and a nitrogen injection tube, 85.0 g of isooctyl acrylate, 10 g of hydroxyethyl acrylate, 3.0 g of acrylamide, and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED lamp to increase the solid content to 18%. Then, 0.05 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0048] The middle layer acrylic resin I and the outer layer acrylic resin II are pumped into the middle cavity and the upper and lower side cavity of the three-layer co-extrusion coating head respectively, and sprayed on the heavy release film through the lip of the coating head, and then covered with the light release film, and finally put into the UV light oven for curing and winding to obtain a three-layer optical adhesive film. The thickness between each layer can be adjusted by the pumping flow of each layer, and the thickness of each layer of the final three-layer optical adhesive film is set to 50μm / 50μm / 50μm.

[0049] Example 4

[0050] 1) Preparation of intermediate layer acrylic resin I:

[0051] In a reaction vessel equipped with a thermometer, a stirrer, and a nitrogen injection tube, 90.0 g of isooctyl acrylate, 5 g of hydroxyethyl acrylate, 4.0 g of acrylic acid, and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 15%. Then, 0.2 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0052] 2) Preparation of outer layer acrylic resin II:

[0053] In a reaction vessel equipped with a thermometer, a stirrer and a nitrogen injection tube, 90.0 g of isooctyl acrylate, 5 g of hydroxyethyl acrylate, 3.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED lamp to increase the solid content to 18%. Then, 0.05 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0054] The middle layer acrylic resin I and the outer layer acrylic resin II are pumped into the middle cavity and the upper and lower side cavity of the three-layer co-extrusion coating head respectively, and sprayed on the heavy release film through the lip of the coating head, and then covered with the light release film, and finally put into the UV light oven for curing and winding to obtain a three-layer optical adhesive film. The thickness between each layer can be adjusted by the pumping flow of each layer, and the thickness of each layer of the final three-layer optical adhesive film is set to 50μm / 50μm / 50μm.

[0055] Comparative Example 1

[0056] Use the same middle layer acrylic resin I as in Example 2;

[0057] Preparation of outer layer acrylic resin II:

[0058] In a reaction container equipped with a thermometer, a stirrer, and a nitrogen injection tube, 80.0 g of isooctyl acrylate, 15 g of hydroxyethyl acrylate, 5.0 g of acrylic acid, and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED lamp to increase the solid content to 18%. Then, 0.05 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for an adhesive sheet.

[0059] The middle layer acrylic resin I and the two outer layers of acrylic resin II are pumped into the middle cavity and the upper and lower side cavity of the three-layer co-extrusion coating head, and sprayed on the heavy release film through the lip of the coating head, and then covered with the light release film, and finally put into the UV light oven for curing and winding to obtain a three-layer optical adhesive film. The thickness between each layer can be adjusted by the pumping flow of each layer, and the thickness of each layer of the final three-layer optical adhesive film is set to 50μm / 50μm / 50μm.

[0060] Comparative Example 2

[0061] 1) Preparation of middle layer acrylic resin I:

[0062] In a reaction vessel equipped with a thermometer, a stirrer and a nitrogen injection tube, 82.0 g of isooctyl acrylate, 15 g of hydroxyethyl acrylate, 3.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 15%. Then, 0.2 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin composition for adhesive sheets.

[0063] 2) Preparation of outer layer acrylic resin II:

[0064] In a reaction vessel equipped with a thermometer, a stirrer and a nitrogen injection tube, 83.0 g of isooctyl acrylate, 15 g of hydroxyethyl acrylate, 2.0 g of acrylamide and 0.03 g of benzil dimethyl ether were added, and the mixture was stirred and replaced with nitrogen at a wind volume of 100 mL / min. 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 18%. Then, 0.05 g of 1,6-hexanediol diacrylate (HDDA) and 0.2 g of benzyl dimethyl ether were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain an adhesive resin combination for an adhesive sheet.

[0065] The middle layer acrylic resin I and the two outer layers of acrylic resin II are pumped into the middle cavity and the upper and lower side cavity of the three-layer co-extrusion coating head, and sprayed on the heavy release film through the lip of the coating head, and then covered with the light release film, and finally put into the UV light oven for curing and winding to obtain a three-layer optical adhesive film. The thickness between each layer can be adjusted by the pumping flow of each layer, and the thickness of each layer of the final three-layer optical adhesive film is set to 50μm / 50μm / 50μm.

[0066] The adhesive sheets obtained in the above examples and comparative examples were evaluated according to the following evaluation method. The evaluation results are shown in Table 1.

[0067] 1. Re-disassembly test:

[0068] Peel off the light release film, stick it on a clean cover glass with an ink step height of 20μm, remove excess sample along the edge of the cover glass, peel off the heavy release film, and stick it on another piece of the same glass without ink step, put the prepared sample into a high-pressure degassing machine at 45℃, 4kg for degassing for 15min and let it stand for 24h, then put the sample on a heating platform at 80℃, use 50μm thick molybdenum wire to cut the glue layer (cut twice), separate the two pieces of glass after cutting, and tear off the glue layer remaining on the glass: if the molybdenum wire breaks during the cutting process, the cut glue layer appears powdery or granular, the two pieces of glass cannot be separated naturally after cutting, the glue layer remaining on the glass cannot be torn off as a whole, etc., it means that the disassembly performance is poor, otherwise it will be disassembled.

[0069] 2. Filling performance test

[0070] Peel off the light release film, stick it on a clean cover glass with an ink step height of 20μm, remove the excess sample along the edge of the cover glass, peel off the heavy release film, and stick it on another piece of glass without ink steps. Put the prepared sample into a high-pressure degassing machine at 45℃ and 4kg for 15 minutes. After the degassing is completed, let it stand for 24 hours to observe whether new bubbles appear. Prepare 10 samples. If there are no bubbles in all 10 samples, the filling performance is qualified.

[0071] 3. Reliability evaluation

[0072] Reliability refers to the ability of the finished product to withstand bubbles, floating, and peeling under different environmental conditions after the film is attached. The specific evaluation method is as follows: the OCA (glass-adhesive film-display module) assembly of the present invention is placed under 85°C and 85% RH for 1000 hours, and then cooled to room temperature to observe whether bubbles appear. If there are bubbles, it is considered NG, otherwise it is recorded as PASS.

[0073] Table 1

[0074]

[0075] Note: Excellent performance is "PASS" and poor performance is "NG".

[0076] As can be seen from the above table, the adhesive films obtained by Examples 1 to 4 of the technical solution of the present invention have good removability, filling performance and reliability. However, when the outer layer adhesive film uses an acidic monomer in the ingredients, such as Comparative Example 1, or the middle layer adhesive film uses an acidic monomer in the ingredients, such as Comparative Example 2, the reliability of the entire adhesive film deteriorates.

[0077] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An optical adhesive film suitable for full lamination process, characterized in that: The adhesive film has a three-layer structure, wherein: The raw materials of the adhesive film of the middle layer include the following components in parts by weight: 80%-90% C4-C18 acrylate monomer Ⅰ; 5%-15% hydrophilic monomer Ⅰ; 1%-10% acidic monomer; 0.05-0.5% crosslinker Ⅰ; 0.05-0.5% photoinitiator Ⅰ; The raw materials of the adhesive films on both sides include the following components by weight: 80%-90% C4-C18 acrylate monomer II; 5%-15% hydrophilic monomer II; 1%-5% basic monomer; 0.05-0.5% crosslinker II; 0.05-0.5% photoinitiator II.

2. The optical adhesive film suitable for full lamination process according to claim 1, characterized in that: Both photoinitiator I and photoinitiator II use hydrogen abstraction type photoinitiator or cleavage type photoinitiator.

3. The optical adhesive film suitable for full lamination process according to claim 1, characterized in that: The preparation process of the adhesive film of the middle layer is as follows: In a reaction vessel equipped with a thermometer, a stirring device and a nitrogen injection tube, C4-C18 acrylate monomer I, hydrophilic monomer I, acidic monomer and part of photoinitiator I were added, and nitrogen was replaced at a wind volume of 100 mL / min while stirring and mixing evenly. Then, at 1.0 mW / cm 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 15%, and then the crosslinking agent I and the remaining photoinitiator I were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain the adhesive resin composition I required for the middle layer; After that, the adhesive resin composition I obtained above was dripped onto the PET release film, and then another PET release film was covered on the other side of the adhesive resin composition I. The adhesive resin composition I was coated into a sheet with a thickness of 50 μm using a roller, and ultraviolet rays were irradiated using an ultraviolet irradiation device with an irradiation intensity of 5 W / cm 2 , energy is 300mJ / cm 2 , a transparent adhesive sheet is obtained; The preparation process of the adhesive films on both sides is as follows: In a reaction vessel equipped with a thermometer, a stirring device and a nitrogen injection tube, C4-C18 acrylate monomer II, hydrophilic monomer II, basic monomer and part of photoinitiator II were added, and nitrogen was replaced at a wind volume of 100 mL / min while stirring and mixing evenly. Then, at 1.0 mW / cm 2 The mixture was polymerized under a 365 nm LED light to increase the solid content to 18%, and then the crosslinking agent II and the remaining photoinitiator II were added, stirred and dissolved uniformly, and then degassed under a vacuum of 0.95 MPa for 2 hours to obtain the adhesive resin composition II required for the outer layer; After that, the adhesive resin composition II obtained above was dripped onto the PET release film, and then another PET release film was covered on the other side of the adhesive resin composition II. The adhesive resin composition for the adhesive sheet was coated into a sheet with a thickness of 50 μm using a roller, and ultraviolet rays were irradiated using an ultraviolet irradiation device with an irradiation intensity of 5 W / cm 2 , energy is 300mJ / cm 2 , a transparent adhesive sheet was obtained.

Citation Information

Patent Citations

  • OCA composition and preparation method thereof, OCA adhesive tape and flexible display terminal equipment

    CN117820971A

  • Return-disassembly OCA adhesive, turn-disassembly OCA adhesive film and preparation method of turn-disassembly OCA adhesive film

    CN118685119A

Cited By

  • OCA (Optical Clear Adhesive) as well as preparation method and application thereof

    CN121379401A